Incorporating specific combining ability into selective seed harvest significantly increases genetic gain: a simulation study on Korean red pine - Jeon, Koeun; Kim, Ye-Ji; Kang, Kyu-Suk; Sagariya, Christi; Lstibůrek, Milan (Tree genetics & genomes, 2025)
Seed orchards play a crucial role in forestry by supplying genetically improved reproductive material. To enhance the genetic gain in offspring produced through open-pollination, selective seed harvest from top-ranking parental genotypes is commonly practiced. This study develops an optimization framework that jointly considers general and specific combining abilities, effective population size, and fertility variation to maximize genetic gain. Using stochastic simulations parametrized with empirical data from a Korean red pine ( Pinus densiflora Siebold & Zucc.) seed orchard, we demonstrate that current selective seed harvest practices capture only a portion of the potential genetic gain, due to the exclusion of specific combining ability. When male fertility variation was present, specific combining ability contributed up to 78% of the gain attributable to general combining ability and remained a key factor influencing total genetic response. A benchmark scenario reflecting common breeding practice achieved only 53–75% of the gain attainable through the proposed optimization. To sum up, a significant portion of the genetic gain from selective seed harvest under open-pollinated conditions comes from specific combining ability, emphasizing the need for better practices in seed orchard management. An Excel-based tool is provided to perform optimization and support decision-making.